And side by side they wander - Tanzer, Molly (Tordotcom/Tor Publishing Group, 2026)
"An intergalactic art heist by a ragtag group of underqualified misfits. What could go wrong? For three hundred years, humanity's greatest works of art have been on loan at the Greenwood Museum. It was finally time for them to come home...but the alien curators were disinclined to return them. Force was out of the question. Earth's government was clear: They were not going to press the issue. So, all we had was guile and hubris to fuel our little intergalactic art heist. My old friend Tarquin was our leader, but not the captain. That was Tchik-tchik, though whether Tchik-tchik was our insectoid pilot's name or species is still unclear to me. Misora, with her extremely illegal biotech mods, was our muscle. Jack was there to hack the security systems of the biggest museum in the galaxy. He was a sensynth, a sentient synthetic being, and the most powerful machine intelligence on Earth uncorrupted by alien technology. My name is Fennel Tycho. I'd like to tell you I was there because of my expertise in Art History. Truth is, I was there because without me, Jack would not have agreed to go. He was notorious for being difficult to work with-but it was a mistake to think I could make things any easier. A meditation on the nature of love, life, and the "culture of the copy," And Side by Side They Wander asks the question: In a future where there are clones, androids, and a sentient mycelium that creates fungal simulacra, who is real and what is fake?"-- Provided by publisher.